TRPM7 Regulates Axonal Outgrowth and Maturation of Primary Hippocampal Neurons - Turlova, Ekaterina (Mol Neurobiol, 2014)
Transient receptor potential melastatin 7 (TRPM7) is a calcium-permeable divalent cation channel and mediates neuronal cell death under ischemic stresses. In this study, we investigated the contribution of TRPM7 to neuronal development in mouse primary hippocampal neurons. We demonstrated that TRPM7 channels are highly expressed in the tips of the growth cone. Either knockdown of TRPM7 with target-specific shRNA or blocking channel conductance by a specific blocker waixenicin A enhanced axonal outgrowth in culture. Blocking TRPM7 activity by waixenicin A reduced calcium influx and accelerated the polarization of the hippocampal neurons as characterized by the development of distinct axons and dendrites. Furthermore, TRPM7 coprecipitated and colocalized with F-actin and α-actinin-1 at the growth cone. We conclude that calcium influx through TRPM7 inhibits axonal outgrowth and maturation by regulating the F-actin and α-actinin-1 protein complex. Inhibition of TRPM7 channel promotes axonal outgrowth, suggesting its therapeutic potential in neurodegenerative disorders.